Analisis Keefektifan Pembelajaran Online pada Masa Pandemi Covid-19 di MTs At-Taqwa Jampue - Muh. Aslan MT; Rustan Efendy; Hasmiah Herawati (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
The purpose of this study was to obtain information about the effectiveness of the online learning process in the Covid-19 pandemic. The outbreak of the corona virus (covid-19) in Indonesia which continued to increase until early March 2020, the implementation of this system also automatically encourages education practitioners to carry out online learning. Teachers and students are forced to be ready in their implementation, although so far some schools have never done learning with an online system. Through this research, the researcher wants to analyze how effective the implementation of the learning system is from the teacher's perspective. The sample of this study was 35 teachers who teach at the primary school level from public and private schools. The instrument used was a questionnaire distributed online using the ms. form link. Based on the data obtained, shows that the implementation of online learning has been carried out effectively seen from the readiness of the teacher, the ability to use applications, responses and benefits obtained. Keywords: covid-19, effectiveness, online teaching, teacher.